Moral reasoning of cypriot business students: A long way off perfection - Demosthenous, Maz; Krambia-Kapardis, Maria; Demosthenous, Maz (My University, 2010)
The debate of whether males and females have the same level of moral reasoning is one that produces inconclusive results. For many professionals the concept of 'professional ethics' is one that implies that each individual has the moral reasoning capability to allow them to render business judgement without having self-interest to alter or impair their professional responsibility. Evidence in business ethics research suggests that the moral reasoning levels of some business students e.g. accounting students and accountants are in the lower range in comparison to other students and other professionals. The objective of this study is to investigate and report the moral reasoning levels of Cypriot business students and whether there are gender differences. This study uses Kohlberg's moral development theory as a framework and Rest's Defining Issues Test (DIT) as a measuring instrument to measure the moral reasoning of the students. This study found that Cypriot students' level of moral reasoning as measured by the DIT is at a very low level in comparison with other university students and there is no significant difference between the male and female students moral reasoning. Common Ground, Maz Demosthenous, Maria Krambia-Kapardis.
Keywords: Business Ethics; Kohlberg Moral Development Theory; Defining Issues Test; Moral Reasoning; Ethical Decision Making; Business Students